Moluskum Kontagiosum: Tinjauan Klinis dan Penanganannya - Filep Marfil Tarangi; Amanda G. Manuputty (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Molluscum contagiosum (MC) is a skin infection caused by the Molluscipox virus and is common in children and adults with active sexual activity. The disease is characterized by the appearance of small, smooth, papule-shaped lesions that have a hollow in the center (umbiliation). MC transmission takes place through direct contact with contaminated lesions or objects, such as towels and clothing, so the spread is quite wide globally. The diagnosis is established through an anamnesis, clinical examination, and physical evaluation. MC therapy is generally supportive, but in certain cases medical measures such as excision and curettage are required to remove the lesion effectively. The use of topical creams containing Fusidic acid, such as Fucilex cream, is often recommended to prevent secondary infections and speed up the postoperative healing process. Proper and prompt treatment is essential to prevent further complications and speed up the patient's recovery. MC has a psychosocial impact, especially on children, so education to parents and health workers is an important part of the treatment strategy. Prevention can be done through increased personal hygiene and avoidance of contact with contaminated objects. The study emphasizes the importance of a holistic approach in diagnosis, therapy, and education to reduce the prevalence of MC and its impact on public health.